Nutrient contents and stoichiometric characteristics of plant leaf-litter-soil in alpine forest - YANG Hong; LIU Wenjie; LIU Heman; CAO Lihua (浙江大学学报. 农业与生命科学版)
In order to explore the nutrient content, return rate and stoichiometric characteristics of plant leaf-litter-soil in alpine forest, the typical forests of Sejila Mountain in Southeast Tibet were analyzed. The results showed that for the same forest type, the contents of organic carbon (C), total nitrogen (N), total phosphorus (P) and total potassium (K) in 0-10 cm soil layer were the highest, while those in ＞20-30 cm soil layer were the lowest. The contents of total N, total P and total K in the samples were new leaf＞old leaf＞litter＞soil, while the content of organic C was old leaf＞new leaf＞litter＞soil. The stoichiometric ratios of C to N, C to P, and C to K of soil, litter, new and old leaves, respectively, were coniferous forest＞broad-leaved forest. It could be seen that coniferous forest was more conducive to the accumulation of C, and broad-leaved forest was conducive to the accumulation of mineral nutrients of N, P, and K. The stoichiometric ratios of N to P in plant leaves ranged from 2.87-5.27, which were significantly lower than the global average level (16.00). It was indicated that this study area was obviously restricted by N element. The nutrient return rates of N, P, and K were all positive, and generally showed that the broad-leaved forest was higher than the coniferous forest. The results provide data support for scientifically clarifying the plant leaf-litter-soil nutrient cycle of forest ecosystem in Southeast Tibet.